Repeated fractionation and umbel receptacle elongation explain the apparent “panicle with simple umbels” in Ferula species (Apiaceae) - Claßen-Bockhoff, Regine; Ajani, Yousef (Frontiers in Ecology and Evolution, 2025)
IntroductionThe carrot family (Apiaceae) is characterized by umbels with umbellets. Traditionally, these umbels are interpreted as inflorescences. Ontogenetic studies, however, indicate that they do not originate from inflorescence meristems but from flower-like floral unit meristems. These meristems repeatedly fractionate sub-meristems, which give rise to umbellets and flowers. Ferula species usually form double racemes with umbels with umbellets. Few species of the genus, previously grouped in the genus Dorema, however, present “panicles with simple umbels”.MethodsAiming to identify the developmental processes resulting in the different inflorescence appearance, we investigate inflorescence development in Ferula hezarlalehzarica (double racemes with umbels with umbellets) and Ferula aucheri (panicles with simple umbels).ResultsBoth species are andromonoecious (perfect and staminate flowers) and produce huge yellow inflorescences. SEM studies confirm that they share the same developmental patterns. Their development starts with an inflorescence meristem segregating umbel meristems. These pass through two steps of fractionation generating first umbellet meristems and then flower meristems. F. aucheri differs from F. hezarlalehzarica by i) producing several lateral inflorescences apart from one terminal one and ii) extremely elongating the umbel receptacles, thereby separating the umbellets from each other. The unusual branches with simple umbels thus prove to be homologous to umbels with umbellets. Furthermore, F. aucheri shows some intermediate inflorescences with umbellets intermixed with umbels. Considering that umbels and umbellets only differ in one step of fractionation, we interpret this mixture as developmental lability.DiscussionThe study shows that meristem conditions define the character of the umbels as floral units and that developmental processes like fractionation, expansion, and elongation shape their outer appearance. It illustrates that inflorescences can be easily misinterpreted if only adult branching systems are investigated.